Prussian Blue Scavenger Ameliorates Hepatic Ischemia-Reperfusion Injury by Inhibiting Inflammation and Reducing Oxidative Stress - Huang, Yongxin; Xu, Qinyuan; Zhang, Jiang; Yin, Yanze; Pan, Yixiao; Zheng, Yuanyi; Cai, Xiaojun; Xia, Qiang; He, Kang (Frontiers in Immunology, 2022)
Oxidative stress and a series of excessive inflammatory responses are the two critical mechanisms of hepatic ischemia reperfusion associated with many clinical settings such as hepatectomy and liver transplantation. Effective anti-inflammatory and anti-oxidative pharmacological interventions are in urgent need. Here, we report a biocompatible Prussian blue (PB) scavenger with reactive oxygen species (ROS)-scavenging and anti-inflammatory properties, which could be used as a promising therapy for hepatic ischemia reperfusion injury (HIRI). PB scavenger is mainly distributed in the liver after intravenous administration and shows excellent bioactivities to alleviate apoptosis, tissue injury and organ dysfunction after HIRI. PB scavenger protects the tissue via scavenging ROS, reducing neutrophil infiltration and promoting macrophage M2 polarization. In addition, PB scavenger significantly reduces oxidative stress in primary hepatocytes and helps them to restore cell viability under oxidative stress condition. PB scavenger effectively diminishes lipopolysaccharide-stimulated inflammation in RAW 264.7 cells. This research reveals the application of PB scavenger as a novel therapeutic agent for treatment of HIRI, providing an alternative perspective in the treatment of ROS-associated and inflammatory liver diseases.